A reduced graphene oxide-titanium dioxide nanocomposite based electrochemical aptasensor for rapid and sensitive detection of Salmonella enterica - Muniandy, Shalini; Teh, Swe Jyan; Appaturi, Jimmy Nelson; Thong, Kwai Lin; Lai, Chin Wei; Ibrahim, Fatimah; Leo, Bey Fen (Elsevier, 2019)
Recent foodborne outbreaks in multiple locations necessitate the continuous development of highly sensitive and specific biosensors that offer rapid detection of foodborne biological hazards. This work focuses on the development of a reduced graphene oxide‑titanium dioxide (rGO-TiO 2 ) nanocomposite based aptasensor to detect Salmonella enterica serovar Typhimurium. A label-free aptamer was immobilized on a rGO-TiO 2 nanocomposite matrix through electrostatic interactions. The changes in electrical conductivity on the electrode surface were evaluated using electroanalytical methods. DNA aptamer adsorbed on the rGO-TiO 2 surface bound to the bacterial cells at the electrode interface causing a physical barrier inhibiting the electron transfer. This interaction decreased the DPV signal of the electrode proportional to decreasing concentrations of the bacterial cells. The optimized aptasensor exhibited high sensitivity with a wide detection range (10 8 to 10 1 cfu mL −1 ), a low detection limit of 10 1 cfu mL −1 and good selectivity for Salmonella bacteria. This rGO-TiO 2 aptasensor is an excellent biosensing platform that offers a reliable, rapid and sensitive alternative for foodborne pathogen detection. © 2019